CRIMINAL LIABILITY OF PERPETRATORS IN THE CRIME OF PROMOTING ONLINE GAMBLING ON SOCIAL MEDIA - Andi Ahmad Ichsan Hady D; A. M. Syukri Akub; Abd. Asis (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This study aims to analyze criminal liability for people who are involved in online gambling promotions through social media accounts and to analyze current law enforcement of promoting online gambling under the guise of binary options on social media. This study uses empirical normative legal research methods, using a qualitative approach to see the provisions or rules that are faced in a fact or reality that occurs in society. The results of this study are that the act of promoting online gambling on social media can be accounted for as long as the action meets the elements of Article 27 Paragraph (2) of the 2016 ITE Law and in that act, the perpetrator can be held accountable for his actions as contained in Article 44 of the Criminal Code, means the perpetrator who commits the crime of promoting online gambling on social media, their souls are not disabled in growth or impaired and are fully aware of their action. Furthermore, the supposed role of the Police, Prosecutors, and Judges has been confirmed in the legislation, and law enforcers should have carried it out. Then in its application based on the results of research on the actual role of the police in conducting investigations, prosecutors in carrying out prosecutions, and judges who are tasked with adjudicating in the context of law enforcement against Article 27 paragraph (2) of the 2016 UURI ITE which is ideally still not maximized because there are still obstacles, such as quality, quantity, and coordination that hinder the realization of ideal law enforcement against Article 27 paragraph (2) of the 2016 ITE Law.